2020
DOI: 10.3390/su12093861
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use/Land-Cover Changes and Its Contribution to Urban Heat Island: A Case Study of Islamabad, Pakistan

Abstract: One of the essential anthropogenic influences on urban climate is land-use/land-cover (LULC) change due to urbanization, which has a direct impact on land surface temperature (LST). However, LULC changes affect LST, and further, urban heat island (UHI) still needs to be investigated. In this study, we estimated changes in LULC from 1993 to 2018, its warming (positive) and cooling (negative) effect, and their contribution to relative LST (RLST) in the city of Islamabad using satellite remote-sensing data. The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 46 publications
2
40
1
Order By: Relevance
“…Climatic and environmental changes negatively influenced the health of the crops with the passage of time in the following ways: variations in the rainfall (Kimuku & Ngigi, 2017), extreme heat stress, change in the land surface temperature (LST), and migration of the peoples from rural to urban areas (Hussain et al, 2020a;Mukherjee & Singh, 2020). The LST patterns provide helpful information about the environment and, therefore, help understand climate change (Cai et al, 2018;Ding & Shi, 2013;Sadiq Khan et al, 2020). Several factors influence it, such as soil content, vegetation changes, building material utilized inroads, and impervious and pervious surfaces Chaudhuri & Mishra, 2016;Yamamoto & Ishikawa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Climatic and environmental changes negatively influenced the health of the crops with the passage of time in the following ways: variations in the rainfall (Kimuku & Ngigi, 2017), extreme heat stress, change in the land surface temperature (LST), and migration of the peoples from rural to urban areas (Hussain et al, 2020a;Mukherjee & Singh, 2020). The LST patterns provide helpful information about the environment and, therefore, help understand climate change (Cai et al, 2018;Ding & Shi, 2013;Sadiq Khan et al, 2020). Several factors influence it, such as soil content, vegetation changes, building material utilized inroads, and impervious and pervious surfaces Chaudhuri & Mishra, 2016;Yamamoto & Ishikawa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rubber plantation as discussed before is increasing the temperature though it is a type of vegetation. The conversion from nonbuilt land use into build use in campus development will increase the temperature (Sadiq Khan et al, 2020) and it is suggested to plant more farmlike vegetation around the area without rubberlike vegetation or water body.…”
Section: Resultsmentioning
confidence: 99%
“…Urban heat island (UHI) effects are another consequence [115,116]. For instance, [117] identified a 1.52 • C average warming effect in Islamabad from 1993 to 2018, due to the city's increased IS. Thus, knowledge of IS spatial distribution in cities can aid in addressing the urban climate and environmental pollution issues.…”
Section: Discussionmentioning
confidence: 99%